2012
DOI: 10.1120/jacmp.v13i5.3869
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral dose from megavoltage cone‐beam CT imaging for nasopharyngeal carcinoma image‐guided radiation therapy

Abstract: The growing use of cone‐beam computed tomography (CBCT) for IGRT has increased concerns over the additional radiation dose to patients. The in‐field dose of IGRT and the peripheral dose (PD) from kilovoltage CBCT (KV‐CBCT) imaging have been well quantified. The purpose of this work is to evaluate the peripheral dose from megavoltage CBCT (MV‐CBCT) imaging for nasopharyngeal carcinoma IGRT, to determine the correlation of peripheral dose with MU protocol and imaging field size, and to estimate out‐of‐field orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, both studies utilized the pelvic (high dose) imaging hence the peripheral dose could be substantially less if a low dose setting is used. In another study, Jia et al [85] measured the peripheral dose from a MV CBCT system and concluded that the magnitude of its peripheral dose is similar to that of kV CBCT imaging, and that it increases with use of higher dose imaging.…”
Section: Peripheral Dose From Cbct Imagingmentioning
confidence: 95%
“…In addition, both studies utilized the pelvic (high dose) imaging hence the peripheral dose could be substantially less if a low dose setting is used. In another study, Jia et al [85] measured the peripheral dose from a MV CBCT system and concluded that the magnitude of its peripheral dose is similar to that of kV CBCT imaging, and that it increases with use of higher dose imaging.…”
Section: Peripheral Dose From Cbct Imagingmentioning
confidence: 95%
“…Incorporating MV imaging dose into the treatment plan and avoiding daily MVCBCT imaging is advised to reduce excess dose [124]. Other dose limiting recommendations include: use of a posterior CBCT acquisition angle (90-290 degrees) to reduce eye dose [125], utilising topogram feature to move field of view caudally [126] and using the lowest numbers of monitor units possible to acquire MV images [124].…”
Section: Imaging Dosementioning
confidence: 99%